Proteomic profiles of Zika virus‐infected placentas bearing fetuses with microcephaly. Issue 1 (12th November 2021) - Quiñones‐Vega, Mauricio; Velásquez, Erika; Sosa‐Acosta, Patricia; Melo, Adriana; Garcez, Patrícia P.; Nogueira, Fábio C.S.; Domont, Gilberto B.
Abstract: Purpose: Zika virus (ZIKV) transmission to the fetus during pregnancy could enable a collection of severe fetal malformations like microcephaly (MC), termed Congenital Zika Syndrome (CZS). The mechanisms involved in ZIKV transplacental transmission are not fully understood. Experimental Design: Here we aim to identify in placental tissues the deregulated proteins associated with ZIKV‐induced MC using label‐free proteomics. Results: We found proteins associated with DNA damage and gene expression inhibition up‐regulated in infected placentas with no MC fetuses (Z+) compared to the control group (Ctr). Actin filament organization and the immune response were also found deregulated in the Z+ group. In ZIKV‐positive placentas bearing fetuses with MC (MC+) was detected an increase in T cell activation, indicating an elevated immune response. A comparison between MC+ and Z+ groups showed a higher abundance of proteins related to endocytosis and autophagy in MC+, suggesting a higher transcytosis of vesicles with ZIKV particles across the maternal‐fetal interface. Conclusions and Clinical Relevance: Our results suggest that higher expression of integrins in MC+ might be associated with high internalization of the virus since these proteins are known as virus receptors. Similarly, an increased immune response in the placenta and higher infiltration of the virus to the fetus could contribute to the neurological malformation of the CZS.